Primary leptomeningeal melanocytosis: A case report with an autopsy diagnosis - Živković Nikola; Mihailović Dragan; Mijović Žaklina; Jovičić-Milentijević Maja (Vojnosanitetski Pregled)
Introduction. Primary melanocytosis of the leptomeninges is a rare tumor, most likely originating from the melanocytes in the leptomeninges. The average survival is only about 5 months. Case report. A 61- years-old woman presented with headache, amaurosis and hallucinations lasted for two months, and she had been treated at the Clinic for Psychiatry and Clinic for Infectious Diseases. The cerebrospinal fluid analysis showed a lower level of glucose and a higher level of proteins. Small shaded areas of basal leptomeninges and hydrocephalus were found by computed tomography and magnetic resonance imaging. The autopsy showed a dark brown mass on basal leptomeninges with blurred boundaries. No pigmented skin lesions were found. Histopathological analysis revealed a primary leptomeningeal melanocytosis. Conclusion. Primary leptomeningeal melanocytosis is a rare tumor, difficult to diagnose. This case is being presented for its specificity, since this diagnosis is not frequently seen in practice.